Physiological determinants of time to exhaustion during intermittent treadmill running at vVO2max - Midgley, A. W.; McNaughton, L. R.; Carroll, S. (International Journal of Sports Medicine, 2007)
Previous studies have reported large between-subject variations in the time to exhaustion during intermittent running at the velocity at V·O2max (vV·O2max). This study aimed to determine which physiological factors contribute to this variability. Thirteen male runners (age 38.9 ± 8.7 years) each completed five treadmill running tests; two incremental tests to determine V·O2max, vV·O2max, the lactate threshold velocity (vLT) and the running velocity-V·O2 relationship; the third test to determine the time to exhaustion during continuous running at vV·O2max (tlimcont); the fourth to determine the maximal accumulated oxygen deficit (MAOD); the fifth to determine the time to exhaustion during intermittent running at vV·O2max (tlimint). Relief intervals during the intermittent test were run at 70 % vV·O2max. The vLT-vV·O2max difference was significantly correlated with tlimint (r = - 0.70; p = 0.007). The correlation coefficient increased to r = - 0.83 (p < 0.001) when the difference between the relief interval velocity and the vLT was deducted from the vLT-vV·O2max difference (theoretically representing the net depletion of the MAOD during each work/relief interval cycle). The main finding of this study was that 49 % of the variance in tlimint was explained by the vLT-vV·O2max difference, compared to 74 % for tlimcont. However, a further 20 % of unique variance in tlimint could be explained with the inclusion of the relief interval velocity-vLT difference. Theoretically, runners with the largest relief interval velocity-vLT difference will replete their anaerobic capacity to a greater extent during each relief interval, thereby increasing time to exhaustion.